Analysis of Brazilian Emergency Operations Centers in disasters response management - Bertazzo, Tabata Rejane; Nakano, Davi Noboru; Brito, Irineu de [UNESP]; Yoshizaki, Hugo Tsugunobu Yoshida (Elsevier, 2025)
Emergency Operations Centers (EOCs) are structures that aim to integrate different public and private organizations with the aim of coordinating the provision of service operations for cities, such as: traffic control, and operation of traffic lights, incidents with falling trees, rain monitoring, public security, crowd control and assistance to victims of landslides, land and floods. Thus, it can be a challenge for public managers to define an appropriate EOC configuration for their municipalities, especially in those with high frequency of disasters. This paper outlines a typology of EOCs, based on data from Brazilian cities located in the states of São Paulo, Rio de Janeiro, Minas Gerais, and Santa Catarina. Three types of EOCs were identified: Civil Defense Operations Centers (CDOC), Monitoring Operations Centers (MOC), and Public Operations and Civil Defense Centers (POCDC). Each type has specific objectives and operational strategies and play a crucial role in coordinating public and private agencies during disaster situations. This article aims to provide reference models for municipalities facing flood, flash flood, and landslide emergencies—the primary causes of devastation and high mortality rates in the southern region of Brazil, which can be valuable for other emerging countries, such as India, Indonesia, Mexico, Bangladesh, etc. The proposed typology facilitates comparative analysis, adaptation, and implementation of effective strategies. It also allows for the integration of showcased best practices into other systems, aiding in policy development. Additionally, these models foster international knowledge exchange and collaboration in the field of disaster management.
Keywords: Disasters operations management; Emergency coordinating centers; Emergency operations centers; Preparedness; Response